Do the determinants of self-rated health vary among older people with disability, chronic diseases or both conditions in urban Colombia? - Monica Pinilla-Roncancio; Catalina González-Uribe; Diego I. Lucumí
Abstract: Our study aimed to identify the main determinants of self-rated health for individuals aged 60 years or older in Bogotá, Colombia, and if those determinants vary between groups. Data was obtained from the Demographic Health Survey 2011 for Bogotá. Logistic regression models were estimated to identify the determinants of excellent/good self-rated health among people aged 60 years or older living in Bogotá. Moreover, a subgroup analysis was conducted seeking to identify if the determinants changed between groups (men, women, persons with disability, with chronic disease(s), and persons with both disability and chronic disease(s)). The likelihood of reporting an excellent/good self-rated health health decreases when the individual has a disability, a chronic disease or reports that their household income is not enough to cover the basic needs. On the other hand, the odds of reporting excellent/good self-rated health increase when the individual is more educated and reports to receive family support. The subgroup analysis showed that although some determinants are only associated with one group (age with chronic diseases), in general, three main determinants stood out: years of education, socioeconomic status variables and receiving family support. The determinants of self-rated health for older adults in Bogotá differ according to the disability and the chronic disease status. Thus, public policies aiming to improve the levels of health and quality must consider the impacts of those characteristics on individuals' perceptions of their own health.